Assessing beliefs and risk perceptions on smoking and smoking cessation in immigrant Chinese adult smokers residing in Vancouver, Canada: a cross-sectional study. Issue 2 (3rd February 2015) - FitzGerald, J Mark; Poureslami, Iraj; Shum, Jessica
Abstract : Objectives: We aimed to conduct culturally-based participatory research to assess cultural and belief contexts for smoking behaviours within Mandarin and Cantonese communities. Outcome variables were smoking-related knowledge, smoking patterns, attitudes and beliefs, and perceived barriers and facilitators to successful cessation. Design: A community-based approach was applied involving smokers, community key-informants and professionals in study design and implementation. Initially, focus groups were conducted and findings were used to develop study instrument. Participants responded once to study questionnaire after informed consent. Setting: Community based in the Greater Vancouver Area, Canada. Participants: 16 Chinese smokers participated in focus groups and subsequently, 167 current Chinese immigrant (137 males and 30 females) smokers from Mandarin and Cantonese communities, recruited with the help of community agencies and collaborating physicians, were enrolled in a cross-sectional study. Results: We found that a majority believed smoking was harmful on their health. Younger smokers (<35 years of age) did not mind smoking in front of young children compared to older smokers (≥35 years of age) (p<0.001). People with high school or lower levels of education believed that they would benefit more from smoking than suffering from withdrawal symptoms compared to better educated smokers (p<0.05). Mandarin smokers were significantly more likely to encourage others to quit than Cantonese smokers (p<0.05). Many indicated not receiving adequate support from care providers and lack of access to culturally and linguistically appropriate cessation programmes impacted on their ability to quit smoking. Conclusions: Our study highlighted the importance of tobacco beliefs and perceptions among Mandarin and Cantonese speaking immigrants with limited access to healthcare information and for younger smokers whose attention to health consequences of smoking may be limited as well. Study participants were generally aware of the health risks and were willing to quit. Access to appropriate cessation programmes would fulfil their willingness.